Continuatio ad manuductionem organicam. Das ist: Fortsetzung zu der Manuduction oder Hand-Leitung zum Orgl-Schlagen - Samber, Johann Baptist 1654-1717 (Salzburg Mayr, 1707)
The personality and work of the Austrian cathedral organist from the archdiocese of Salzburg, music theorist and court musician Johann Baptist Samber, have so far been little researched. His writings offer information on performance practice, organ music or organ building, basso continuo, counterpoint, musical rhetoric and solmisation. Samber, who describes himself as a pupil of Andreas Hofer and Georg Muffat, wrote three important works on composition: the 'Manuductio ad organum' (1704; see 04C06c), a 'Hand-Leitung zum Orgl-Schlagen', its sequel, the present 'Continuatio ad manuductionem organicam' (1707), and the 'Elucidatio musicæ choralis' (1710; this convolute). It is characteristic of the first two works that Samber's instrumental and compositional instruction is based almost exclusively on the basso continuo and the traditional voice leading rules. Significant are his careful and detailed descriptions and remarks on German fugue compositions of the late 17th century.
Bound in with 'Elucidatio musicæ choralis'
Ex Libris Alfred Cortot (plate) and Sambure (information provided by TK)
Worinnen haubtsächlich vier hernachfolgende Unterweisungen begriffen seynd ... Allen Liebhabern der Edlen Musci-Kunst zu Gefallen und Nutzlicher Ergetzlichkeit ...
Keywords: 18th Century (1701-1800); Method; Music theory; Organ music; Chorale; Prelude; Fugue; Salzburg (Austria); muziek =; diminuties; emoties; solmisatie; Gaffurio, F; tekstplaatsing; tekstuitspraak; transponeren; tritonus; kerktoonsoorten; Kircher, A; Egedacher, J.C.; hexachordmutatie; kopieerfouten; Ornithoparcus, A; Reinspeck, M; Scheyerer, B; Tevo, Z